Evaluating gifted education in Palestine: A study of educational and learning capitals - Anies Al-Hroub (Cogent Education, 2023)
AbstractThe present theoretical article aims to conduct a critical analysis and elaborate on the influence of educational and learning capitals on the education of gifted students in Palestine. The article commences by providing a comprehensive examination of the educational system in Palestine, offering an overview of the current state of gifted education in the country, along with its challenges and expenditures by both public and private educational institutions. The Education and Learning Capital Model (ELCM), based on the Systems Theory and the Actiotope Model of Giftedness was used as a framework to study and explain the current practices of gifted education in Palestine. Accordingly, the article provides a detailed discourse on the ten educational and learning capitals in the context of gifted education in Palestine. This is done by drawing upon relevant, evidence-based literature as a basis to identify the critical elements that contribute to the academic success of gifted students in Palestine. The article further highlights key insights into the cost of gifted education, including the resources required for implementing effective educational programs for gifted individuals. Additionally, the article emphasizes the significance of recognizing and defining giftedness in Palestine, along with teacher training for providing adequate support to these students. Finally, the article concludes by emphasizing the importance of efficient utilization of educational resources for gifted students to ensure their academic achievement and growth, while also addressing the challenges faced by the gifted education system in Palestine.